STYLISTIC FEATURES OF R.M. RILKE’S POETRY AND QUESTIONS OF THEIR TRANSLATION INTO ENGLISH - N. V. Voronevskaya (Концепт: философия, религия, культура, 2019)
The article is devoted to the analysis of peculiarities of recreating the stylistic features of R. M. Rilke’s poetry into English, i.e. to English rendering of the shortened line as an innovative element of the sonnet form of the lyrical cycle “Sonnets to Orpheus”. Rilke’s works have been translated into all languages of the world. Outside of the German-speaking world, his poetry and prose is best known in the USA and Great Britain. This article presents a comparative analysis of the English translations of the 19th sonnet of the frst part of the cycle, performed by more than twenty English translators. The cycle “Sonnets to Orpheus” has been translated into English more than twenty times. The images and themes of the sonnets, as well as their unique, author-modifed style, turned out to be interesting for several English generations of Rilke’s translators. These translators entered the so-called “the correspondence competition”: to test their talent and convey the beauty of the Rilke’s sonnets by means of English. The analysis of the original and its English translations showed that the shortened line as a peculiar feature of the 19th sonnet’s style is a certain difculty to recreate in English, and Rilke’s translators only partly conveyed the rhythmic structure of the original. The most adequately recreating stylistic features of the 19th sonnet translations were performed by American authors: J. Lemont and L. Norris. In their translations, the shortened line as a distinctive feature of the style of the 19th sonnet is most closely to Rilke’s original.